The Growth of Relic and Icon Veneration in the Eastern Roman Empire During the Reigns of Justinian and His Successors (527-602) and Their Impact on the Hyper-Sacralisation of Imperial Power - Lamadeleine, Justin (Université d'Ottawa | University of Ottawa, 2025)
Abstract The evolution of the cultural and political landscapes of the eastern Roman empire during the sixth century presents many challenges for scholars. The emperor Justinian and his successors reigned during a dynamic and turbulent period of cultural and political change. For two centuries, Christianity had taken shape within the eastern Roman empire by developing its own traditions. By the end of the sixth century, Christianity encompassed all aspects of eastern Roman society. It impacted the cultural and political landscape in which the emperors of the Justinianic dynasty displayed their imperial authority and promoted their ideologies. Yet classical culture and mentalities had not disappeared. In fact, at times, antiquarian or classical mentalities informed Christian innovations and were often integrated within the new Christian landscape. By the sixth century, however, the continuation of the classical tradition had the potential to create tensions within the Christianising empire. We are thus left at a crossroads between two seemingly contradictory traditions during a period of cultural and political transition. This is the cultural background that shaped the imperial ideologies of the emperor Justinian and his successors. This thesis brings together in one coherent study three widely debated topics in academia and sheds new light on the impact of Christianity on the cultural and political evolution of the eastern Roman empire during the reigns of the emperors of the Justinianic dynasty. The primary concern of this thesis is the integration of Christianity within the imperial ideologies of the emperor Justinian and his successors at the same time as they tried to promote Roman imperial renewal or restoration during a period of transition. Previous scholarly contributions paved the way for further research of the topic at hand and several approaches have been presented in academia, but the nature of this evolution remains obscure. This thesis offers a different approach by combining three ongoing debated topics, namely the rise and growth of relic and icon veneration in Late Antiquity, the hyper-sacralisation of imperial power, and the Christianisation of eastern Roman society during the sixth century. By examining the primary Greek, Latin and Syriac sources, this thesis argues that Christian cults of veneration, namely those of the saints, their relics and icons, impacted the cultural and political evolution of the sixth century, particularly in regard to imperial ideologies.
Keywords: Late Antiquity; Sixth century; Imperial ideology; Hyper-sacralisation; Christianisation; Icons; Relics